Alcohol Use, Stigmatizing/Discriminatory Attitudes, and HIV High-Risk Sexual Behaviors among Men Who Have Sex with Men in China. (27th March 2014) - Liao, Meizhen; Kang, Dianmin; Tao, Xiaorun; Bouey, Jennifer Huang; Aliyu, Muktar H.; Qian, Yuesheng; Wang, Guoyong; Sun, Xiaoguang; Lin, Bin; Bi, Zhenqiang; Jia, Yujiang
Abstract : Objective . This research was conducted to assess the correlates of alcohol consumption and HIV/AIDS-related stigmatizing and discriminatory attitudes among men who have sex with men (MSM) in Shandong province, China. Methods . A cross-sectional survey provided demographics, sexual behaviors, illicit drug use, alcohol consumptions, and service utilization. Results . Of 1, 230 participants, 82.8% were single, 85.7% aged <35 years, 47.2% had college or higher education, and 11.7% drank alcohol >3 times per week in the past six months. The average total score of stigmatizing and discriminatory attitude was 37.4 ± 4.4. More frequent episodes of alcohol use were independently associated with higher levels of HIV/AIDS-related stigma and discrimination, unprotected anal sex, bisexual identity, multiple male sex partners, drug use, and lower levels of education. Expressing higher levels of HIV/AIDS-related stigmatizing and discriminatory attitudes was independently associated with alcohol use, unprotected male anal sex, bisexuals, more male sex partners, commercial sex with men, and non-receipt of peer education in the past year. Conclusion . HIV/AIDS-related stigmatizing and discriminatory attitudes are common and associated with alcohol use and unprotected sex among MSM. The finding highlights the needs to develop programs that would reduce HIV/AIDS-related stigmatizing and discriminatory attitudes and strengthen alcohol use prevention and risk reduction initiatives among MSM.